Penerapan Metode Tartil dalam Meningkatkan Kemampuan Membaca al-Qur’an Santri di Pondok Pesantren Darussalam Sengon Jombang - Esty Lia Sukma Dewi; Lintang Ramadhani; Hilyah Ashoumi (Lembaga Yasin AlSys, 2026)
Although structured Qur’an learning has received attention in a number of studies, research that specifically examines the detailed process of implementing the Tartil method, as well as its supporting and inhibiting factors in the pondok pesantren environment, remains limited. This study aims to describe the implementation of the Tartil method, the improvement of students’ Qur’an reading ability, and its supporting and inhibiting factors at Pondok Pesantren Darussalam Sengon Jombang. This study employed a qualitative approach with a case study design involving seven informants selected purposively, consisting of the pengasuh, curriculum coordinator, teacher, and students. Data were collected through participant observation, in-depth interviews, and documentation, and were then analyzed using the Miles, Huberman, and Saldana model through the stages of data condensation, data display, and conclusion drawing. The findings showed that the implementation of the Tartil method was carried out systematically through the stages of talqin-ittiba', the 3M method (Listening, Imitating, Seeing), and continuous evaluation, and was proven effective in improving the accuracy of makharijul huruf, compliance with tajwid rules, and the students’ reading fluency. The main supporting factors included teacher competence, a religious and disciplined pesantren environment, adequate learning facilities, and the students’ intrinsic motivation. The inhibiting factors included differences in the students’ initial abilities, lack of concentration, limited learning space during the rainy season, and limited teacher availability at certain times. The conclusion of this study confirms that the Tartil method plays an important role in systematically improving the quality of the students’ Qur’an recitation. These findings contribute to the development of the literature on Qur’anic pedagogy and provide practical implications for pondok pesantren to strengthen teacher training, maintain a conducive learning environment, and develop adaptive strategies to overcome physical and motivational barriers. This study also opens opportunities for further research on the long-term retention of Tartil method-based skills and its comparative effectiveness with other methods, such as Ummi or Tilawati.